On reading - C. Perrin (Law Text Culture, 1998)
Justin Clemens' review of our previous issue was short if not sweet. The invective contained in it, together with the refusal of the Australian Book Review to publish a response, has obliged us to republish the review together with a brief reply from the special editor of that issue.